1975
DOI: 10.1901/jeab.1975.24-43
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSE‐RATE INVARIANCE IN CONCURRENT SCHEDULES: EFFECTS OF DIFFERENT CHANGEOVER CONTINGENCIES1

Abstract: In a two-key chamber, one key (the food key) was either red or green with different variable-interval schedules operating concurrently in each color and a second key (the changeover key) served to change the food-key color. Three pigeons were trained with either a 2-sec changeover delay or a 0-sec changeover delay and three birds with a fixed-ratio 2 on the changeover key instead of a changeover delay. The proportion of time spent in red approximated the proportion of reinforcers delivered in red for all birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…Similar results were reported by Bourland and Miller (1978) and Killeen (1972). On the other hand, Guilkey, Shull, and Brownstein (1975) and White (1979) failed to observe this rate difference when they used a FR changeover requirement. Pliskoff, Cicerone, and Nelson (1978) …”
Section: ()Jsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were reported by Bourland and Miller (1978) and Killeen (1972). On the other hand, Guilkey, Shull, and Brownstein (1975) and White (1979) failed to observe this rate difference when they used a FR changeover requirement. Pliskoff, Cicerone, and Nelson (1978) …”
Section: ()Jsupporting
confidence: 83%
“…Second, it was consistently found that the differences between COD and post-COD response rates were greatly reduced when a COD of variable, rather than fixed, duration was used. Other researchers (Guilkey et al, 1975;Pliskoff et al, 1978;White, 1979) have also failed to obtain a substantial increase in response rates immediately after the CO response when they used a FR changeover requirement instead of a COD of fixed duration. The results of their experiments together with the present findings indicate that elevated response rates immediately after the CO response may occur only when a COD of fixed duration is used.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the two methods have similar effects: the matching re-239 1979,31,[239][240][241][242][243][244][245][246][247][248][249][250][251][252] NUMBER 2 (MARCH) lation is found when either is used, and increasing the value of each has a similar effect on changeover and response rates. One important difference noted by Guilkey et al (1975) is that the COR does not produce the postchangeover bursts of responding which occur during the COD. With respect to this, it should be recognized that the COD is imposed after the requirement for switching has been met, whereas the COR is simply a requirement for switching.…”
mentioning
confidence: 98%
“…Thus reinforcements on one schedule are separated from responses on the other by a series of responses on the changeover manipulandum. Comparisons of the use of a COR and a COD in concurrent variable-interval (VI) schedules have been made by Guilkey, Shull, and Brownstein (1975) and Stubbs and Pliskoff (1969), both using pigeons. In general, the two methods have similar effects: the matching re-239 1979,31,[239][240][241][242][243][244][245][246][247][248][249][250][251][252] NUMBER 2 (MARCH) lation is found when either is used, and increasing the value of each has a similar effect on changeover and response rates.…”
mentioning
confidence: 99%
“…For example, the changeover delay or COD (Herrnstein, 1961) arranges a time interval after each changeover from one response to the other, during which no response can be reinforced. But although a COD may reduce the likelihood that either response is maintained by reinforcers scheduiled for the other, it also affects the rate and pattern of responding immediately after the changeover (Catania, 1972;Guilkey, Shull, and Brownstein, 1975;Pliskoff, 1971;Silberberg and Fantino, 1970). Thus, the properties of concurrent performances may depend critically on whether and at what delay value a COD operates (Catania, 1962(Catania, , 1963Shull and Pliskoff, 1967).…”
mentioning
confidence: 99%